Cognitive function in outpatients with perceived chronic stress - Öhman, Lena; Nordin, Steven; Bergdahl, Jan; Slunga Birgander, Lisbeth; Stigsdotter Neely, Anna (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'The number of employees on sick leave due to stress-related syndromes has increased drastically in many industrialized countries. Cognitive dysfunction is a common complaint among patients suffering from chronic stress. Previous research on chronic stress has mainly focused on its interpersonal, attitudinal, psychological, organizational, and physical effects. Less attention has been allocated to effects of chronic stress on cognitive functioning. Hence the aim of the present study was to investigate the relationship between chronic stress and cognition. ' ' METHODS ': 'The cognitive performance of 19 chronic stress outpatients and 19 matched controls was studied. A battery of standard and experimental cognitive tests assessing processing speed, attention, working memory, and episodic and semantic memory were administered. ' ' RESULTS ': 'Performance deficits of the chronic stress patients relative to the performance of the controls were found for some but not all cognitive tasks, indicating a selective deficit. Deficits were found for episodic memory, particularly for learning across repeated trials and for tasks requiring divided attention during either the encoding or retrieval of words. Performance differences were also found for aspects of working memory, mental tempo, semantic access, and prospective memory, but not for basic perceptual speed measures. ' ' CONCLUSIONS ': 'These findings may suggest suboptimal executive functioning (eg, strategic or attentional control) among chronic stress patients. Particularly, poor performance in letter fluency and prospective memory were significantly associated with chronic stress, the finding suggesting the usefulness of these tests as clinical tools in evaluations of chronic stress states.
Keywords: burnout; cognitive function; executive functioning; memory; outpatient; perceived chronic stress; self-assessment; self-report; work stress